Molecular epidemiology of Acinetobacter baumannii and Acinetobacter nosocomialis in Germany over a 5‐year period (2005–2009). (3rd October 2012) - Schleicher, X.; Higgins, P. G.; Wisplinghoff, H.; Körber‐Irrgang, B.; Kresken, M.; Seifert, H.
Abstract: To investigate the species distribution within the Acinetobacter calcoaceticus–Acinetobacter baumannii complex and the molecular epidemiology of A. baumannii and Acinetobacter nosocomialis, 376 Acinetobacter isolates were collected prospectively from hospitalized patients at 15 medical centres in Germany during three surveillance studies conducted over a 5‐year period. Species identification was performed by molecular methods. Imipenem minimum inhibitory concentrations (MIC) were determined by broth microdilution. The prevalence of the most common carbapenemase‐encoding genes was investigated by oxacillinase (OXA) ‐multiplex polymerase chain reaction (PCR). The molecular epidemiology was investigated by repetitive sequence‐based PCR (rep‐PCR; DiversiLab™). Acinetobacter pittii was the most prevalent Acinetobacter species ( n  = 193), followed by A. baumannii ( n  = 140), A. calcoaceticus ( n  = 10) and A. nosocomialis ( n  = 8). The majority of A. baumannii was represented by sporadic isolates ( n  = 70, 50%) that showed unique rep‐PCR patterns, 25 isolates (18%) clustered with one or two other isolates, and only 45 isolates (32%) belonged to one of the previously described international clonal lineages. The most prevalent clonal lineage was international clone (IC) 2 ( n  = 34) and IC 1 ( n  = 6). According to CLSI, 25 A. baumannii isolates were non‐susceptible to imipenem (MIC ≥ 8 mg/L), all of which produced an OXA‐58‐like or OXA‐23‐like carbapenemase. The rate of imipenem susceptibility among A. baumannii isolates decreased from 96% in 2005 to 76% in 2009. All other Acinetobacter isolates were susceptible to imipenem. The population structure of carbapenem‐susceptible A. baumannii in Germany is highly diverse. Imipenem non‐susceptibility was strongly associated with the clonal lineages IC 2 and IC 1. These data underscore the high clonality of carbapenem‐resistant A. baumannii isolates.